The LuxR Regulators PcoR and RfiA Co-regulate Antimicrobial Peptide and Alginate Production in Pseudomonas corrugata - Licciardello, Grazia; Caruso, Andrea; Bella, Patrizia; Gheleri, Rodolpho; Strano, Cinzia P.; Anzalone, Alice; Trantas, Emmanouil A.; Sarris, Panagiotis F.; Almeida, Nalvo F.; Catara, Vittoria (Frontiers in Microbiology, 2018)
Cyclic lipopeptides (CLPs) are considered as some of the most important secondary metabolites in different plant-associated bacteria, thanks to their antimicrobial, cytotoxic and surfactant properties. In this study, our aim was to investigate the role of the Quorum Sensing system (QS), PcoI/PcoR and the LuxR-type transcriptional regulator RfiA in CLP production in the phytopatogenic bacterium, Pseudomonas corrugata based on our previous work where we reported that the pcoR and rfiA mutants were devoid of the CLPs cormycin and corpeptin production. Due to the close genetic link between the QS system and the RfiA (rfiA is co-transcribed with pcoI), it was difficult to ascertain the specific regulatory role in the expression of target genes. A transcriptional approach was undertaken to identify the specific role of the PcoR and RfiA transcriptional regulators for the expression of genes involved in CLP production. The RNA-seq based transcriptional analysis of the wild type strain CFBP 5454 in comparison with GL2 (pcoR mutant) and GLRFIA (rfiA mutant) was performed in cultural conditions favoring CLP production. Differential gene expression revealed that 152 and 130 genes have significantly different levels of expression in the pcoR and rfiA mutants, respectively. Of these, the genes linked to the biosynthesis of CLPs and alginate were positively controlled by both PcoR and RfiA. Blast homology analysis showed that 21 genes in a large CLP biosynthetic cluster involved in the production of three antimicrobial peptides, which span approximately 3.5% of the genome, are strongly over-expressed in the wild type strain. Thus, PcoR and RfiA function mainly as activators in the production of bioactive CLPs, in agreement with phenotype analysis of mutants. RNA-seq also revealed that almost all the genes in the structural/biosynthetic cluster of alginate exopolysaccharide (EPS) are under the control of the PcoR-RfiA regulon, as supported by the 10-fold reduction in total EPS yield isolated in both mutants in comparison to the parent strain. A total of 68 and 38 gene expressions was independently regulated by PcoR or RfiA proteins, respectively, but at low level. qPCR experiments suggest that the growth medium and plant environment influence the expression ofCLP and alginate genes.